2021
DOI: 10.1155/2021/8883700
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infection among Cancer Patients: Analysis of Isolates and Antibiotic Sensitivity Pattern

Abstract: Introduction. Cancer patients being immunosuppressed are vulnerable to develop infections. Knowledge of the changing epidemiology of infections has a pivotal role in its management. Aims and Objectives. The study is undertaken to assess the types of bacterial infections in cancer patients undergoing anticancer treatment, the associated bacterial pathogens, and their antibiotic sensitivity patterns. Materials and Methods. A retrospective surveillance study was undertaken in our center. Positive culture reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 17 publications
6
27
4
Order By: Relevance
“…BGNs showed greater resistance to aminopenicillins, fourth generation cephalosporins, uoroquinolones, second and rst generation cephalosporins and aminoglycosides, in agreement with the results of a study in India carried out with 66 cases of bloodstream infection 40 . Increased resistance to carbapenems, combinations of beta-lactamase inhibitors, beta-lactamase, aminoglycosides, uoroquinolones and cephalosporins (including high resistance to cefepime) has been observed 41 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…BGNs showed greater resistance to aminopenicillins, fourth generation cephalosporins, uoroquinolones, second and rst generation cephalosporins and aminoglycosides, in agreement with the results of a study in India carried out with 66 cases of bloodstream infection 40 . Increased resistance to carbapenems, combinations of beta-lactamase inhibitors, beta-lactamase, aminoglycosides, uoroquinolones and cephalosporins (including high resistance to cefepime) has been observed 41 .…”
Section: Discussionsupporting
confidence: 88%
“…And the occurrence of vancomycin-resistant Enterococcus was 7,7%, similar to that found by Bhat et al, (2021) 40 . The prevalence of vancomycin-resistant enterococci (VRE) has become stable or decreasing after 2012 42 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Cancer patients who are undergoing anticancer treatment have severely weakened immune systems; thus, they are more vulnerable to bacterial infections and their life-threatening complications. A previous retrospective surveillance study revealed that the most common associated bacterial pathogens were Klebsiella pneumonia and Enterococcus faecium (bloodstream), Pseudomonas aeruginosa (respiratory tract), Escherichia coli (in urinary tract), Staphylococcus aureus and S. epidermidis (skin and soft tissues) [ 18 ]. It is worth noting that some of these microbes are rather difficult to treat, as they are considered to be drug-resistant isolates [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress promotes genomic instability, tumorigenesis, metastasis, and cancerous cell proliferation [3,4]. The cancer patients being immunosuppressed are more vulnerable to get bacterial infection [5]. Therefore, consideration of both anticancer and antibacterial aspects of treatment is mandatory.…”
Section: Introductionmentioning
confidence: 99%